Electrochemical Immunosensors: The Evolution from Elisa to EμPADs. Issue 4 (26th October 2022) - Ochoa‐Ruiz, Andrea Gabriela; Parra, Guillermo; López‐Espinoza, Diego; Astudillo, Pablo; Galyamin, Dmitry; Sabaté, Neus; Esquivel, Juan Pablo; Vallejo‐Cardona, Alba Adriana
Abstract: Electrochemical immunosensors comprise the merging of two different disciplines: molecular biology and electrochemistry. This review explains in depth the main parts of electrochemical immunosensors and how the enzyme‐linked immunosorbent assay (ELISA) has been integrated into sophisticated "lab‐on‐a‐chip" and "point‐of‐care" devices. It also reviews how nanotechnology has been a powerful tool for achieving lower detection limits, more signal amplification, and constructing label‐free devices. It finally explores the new perspectives on electrochemical immunosensors to integrate them in novel paper microfluidic devices called EμPADs. Colleagues introducing themselves to the topic for the first time will find in this review a comprehensive revision of how the basics of the technology have given rise to the emerging topic of EμPADs. Abstract :